2014
DOI: 10.1155/2014/936891
|View full text |Cite
|
Sign up to set email alerts
|

ATP Release through Lysosomal Exocytosis from Peripheral Nerves: The Effect of Lysosomal Exocytosis on Peripheral Nerve Degeneration and Regeneration after Nerve Injury

Abstract: Studies have shown that lysosomal activation increases in Schwann cells after nerve injury. Lysosomal activation is thought to promote the engulfment of myelin debris or fragments of injured axons in Schwann cells during Wallerian degeneration. However, a recent interpretation of lysosomal activation proposes a different view of the phenomenon. During Wallerian degeneration, lysosomes become secretory vesicles and are activated for lysosomal exocytosis. The lysosomal exocytosis triggers adenosine 5′-triphospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 63 publications
(88 reference statements)
1
33
0
1
Order By: Relevance
“…The involvement of ATP in peripheral (including enteric) nerve degeneration and regeneration has also been studied (see Tokui et al, 1994;Sch€ afer et al, 1995;Xu et al, 2013;Jung et al, 2014), but will not be covered in this review article, which is focussed on the CNS.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…The involvement of ATP in peripheral (including enteric) nerve degeneration and regeneration has also been studied (see Tokui et al, 1994;Sch€ afer et al, 1995;Xu et al, 2013;Jung et al, 2014), but will not be covered in this review article, which is focussed on the CNS.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Astrocytes then respond to microglialderived ATP via P2Y1 receptors to trigger neuroprotection through secretion of interleukin-6 [74]. It has been shown that the microglial ATP is stored in secretory lysosomes and exocytosed upon stimulation [116]. This released ATP may act as an autocrine or paracrine messenger and trigger ATP secretion, resulting in stimulation of cell migration.…”
Section: Roles Of Vesicular Atp Releasementioning
confidence: 99%
“…This released ATP may act as an autocrine or paracrine messenger and trigger ATP secretion, resulting in stimulation of cell migration. This may provide a positive feedback mechanism to ensure migration and accumulation of microglia towards the site of injury [69,116]. In the microglia of VNUT −/− mice, neither vesicular ATP release nor ATP-dependent secondary responses are observed [75].…”
Section: Roles Of Vesicular Atp Releasementioning
confidence: 99%
See 1 more Smart Citation
“…In degenerating neurons, it has been suggested that cathepsins can be released directly into the cytoplasm after the disruption of lysosomes, with detrimental consequences for the cell (Bidere et al, 2003; Boland and Campbell, 2004; Kagedal et al, 2001; Roberg and Ollinger, 1998). In addition to their intracellular localization, cathepsins may be released outside of a cell through leakage from the endosomal-lysosomal system [reviewed in (Aits and Jaattela, 2013; Pislar and Kos, 2014)] and lysosomal exocytosis [reviewed in (Andrews, 2000; Blott and Griffiths, 2002; Jung et al, 2014; Sundler, 1997)]. In the brain, activated microglia secrete several proteases including Cat B (Buck et al, 1992).…”
Section: Cathepsins and Cysc Can Interact In Multiple Cellular Commentioning
confidence: 99%